Experimental study of an ORC (Organic Rankine Cycle) and analysis of R1233zd-E as a drop-in replacement for R245fa for low temperature heat utilization. (15th May 2016) - Eyerer, Sebastian; Wieland, Christoph; Vandersickel, Annelies; Spliethoff, Hartmut
Abstract: The Organic Rankine Cycle can be applied to convert low temperature heat to electrical power using organic working fluids. Recently, a new generation of working fluids has been introduced with almost no Ozone Depletion Potential and significantly smaller Global Warming Potential, compared to currently used refrigerants. R1233zd-E is a promising low-GWP (global warming potential) alternative to R245fa, a widely used fluid in ORC (Organic Rankine Cycle) systems. This paper analyzes the applicability of the new fluid as drop-in replacement for R245fa in existing systems and compares system parameters such as cycle efficiency and power output. To this end, the influence of the process parameters mass-flow rate, condensation temperature and expander rotational speed is investigated experimentally for both fluids. The test rig used has an electrical heater as a heat source and a scroll compressor as an expander. As a conclusion, R1233zd-E can be used as a substitute for R245fa in existing ORC systems. In addition to the advantage of having a much smaller GWP, the use of R1233zd-E may lead to higher thermal efficiencies. Comparing the highest achieved thermal efficiency, R1233zd-E performs 6.92% better than R245fa. However, comparing the maximal gross power output, R245fa performs 12.17% better than R1233zd-E. Highlights: The use of R1233zd-E as drop-in replacement for R245fa in an ORC system is analyzed. R1233zd-E is an appropriate alternative for R245fa with significantly reduced GWP. The application of R1233zd-E may lead to higher thermal efficiencies. Comparing maximum thermal efficiencies, R1233zd-E performs 6.9% better than R245fa.